THE EXPLORATION OF GENRE BASED APPROACH IN TEACHING SPEAKING AT EFL CLASSROOM: A CASE STUDY AT STUDENT HIGH SCHOOL - Kezia Nathalia Graziella; Yogi Setia Samsi; Acep Bahrul Kamil (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Speaking is a crucial thing in life and the main form of communication. In this era Indonesia using a